FK506-Binding Protein like (FKBPL) Has an Important Role in Heart Failure with Preserved Ejection Fraction Pathogenesis with Potential Diagnostic Utility - Michael Chhor; Hao Chen; Djurdja Jerotić; Milorad Tešić; Valentina N. Nikolić; Milan Pavlović; Rada M. Vučić; Benjamin Rayner; Chris J. Watson; Mark Ledwidge; Kenneth McDonald; Tracy Robson; et al. (Biomolecules, 2023)
Heart failure (HF) is the leading cause of hospitalisations worldwide, with only 35% of patients surviving the first 5 years after diagnosis. The pathogenesis of HF with preserved ejection fraction (HFpEF) is still unclear, impeding the implementation of effective treatments. FK506-binding protein like (FKBPL) and its therapeutic peptide mimetic, AD-01, are critical mediators of angiogenesis and inflammation. Thus, in this study, we investigated—for the first time—FKBPL’s role in the pathogenesis and as a biomarker of HFpEF. In vitro models of cardiac hypertrophy following exposure to a hypertensive stimulus, angiotensin-II (Ang-II, 100 nM), and/or AD-01 (100 nM), for 24 and 48 h were employed as well as human plasma samples from people with different forms of HFpEF and controls. Whilst the FKBPL peptide mimetic, AD-01, induced cardiomyocyte hypertrophy in a similar manner to Ang-II (p < 0.0001), when AD-01 and Ang-II were combined together, this process was abrogated (p < 0.01–0.0001). This mechanism appears to involve a negative feedback loop related to FKBPL (p < 0.05). In human plasma samples, FKBPL concentration was increased in HFpEF compared to controls (p < 0.01); however, similar to NT-proBNP and Gal-3, it was unable to stratify between different forms of HFpEF: acute HFpEF, chronic HFpEF and hypertrophic cardiomyopathy (HCM). FKBPL may be explored for its biomarker and therapeutic target potential in HFpEF.